THE INFLUENCE OF COHESIVENESS AND LEADERSHIP ON THE PERFORMANCE OF CIREBON EMPLOYEES - Barra Purnama Pradja; Sandi Nasrudin Wibowo; Ade Solahudin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to find out and analyze the influence of cohesiveness and leadership both partially and simultaneously on the performance of Grage Mall Cirebon employees. The type of research used is descriptive quantitative using statistical tests using the SPSS softwere tool version 21.0. In this study, the population was all employees of Grage Mall Cirebon which amounted to 53 employees. As for the sampling technique, it uses saturated sampling. The data collection methods used are field studies, questionnaires, interviews and literature studies. The analysis used is multiple linear regression analysis. The results of this study concluded that the cohesiveness variable partially affects employee performance with a t value calculated > t table, namely 2.096 > 2.008 and has a significant value smaller than 0.05 or 0.041< 0.05. Variabel leadership partially affects performance with a t value calculated > ttable which is 12,825>2,008 and has a significant value smaller than 0.05 or 0.000 Ftable which is 106,940>3.18 and has a significant value smaller than the level of thevalue of 0.05 or 0.000 < 0.05.